Revision of the Ambrysus signoreti Stål species complex (Heteroptera: Naucoridae: Ambrysinae). Section 2. - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2023)
The Ambrysus signoreti Stål species complex was recently diagnosed and subdivided into three sections based on morphology of the female subgenital plate. In the present study, the species in the second section, characterized by the posterior margin of the subgenital plate with central lobe extending posteriorly further than the posterolateral corners, are revised. Supplemental descriptions for four species described by La Rivers and Usinger are provided. The group includes six species: four from Mexico (Ambrysus brailovskyi Reynoso & Sites, A. henryi Reynoso & Sites, A. inflatus La Rivers, A. lundbladi Usinger), one from Mexico and the United States (A. lunatus Usinger), and one from Costa Rica (A. harmodius La Rivers). Also, the subspecies A. lunatus menoides La Rivers is proposed as a junior synonym of A. lundbladi. We herein report for the first time characteristics of the previously unknown male of A. lundbladi. Additionally, we present new state records from Mexico for A. inflatus and A. lundbladi, and new province records from Costa Rica for A. harmodius. Finally, an illustrated key to the species in the second section of the complex is provided.